Theoretical review: the dividend policy / Wan Mardyatul Miza Wan Tahir and Ja'izah Abdul Jabar - Wan Tahir, Wan Mardyatul Miza; Abdul Jabar, Ja'izah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The theoretical review explains the underlying rationale of dividend policy. The dividend policy theory is well-known by the work of Miller and Modigliani (1961) on irrelevance theory. They demonstrated that dividend policy was irrelevant to the market value of a company under restricted assumptions including rational investor and perfect capital market. Consequently, this attracted many other researchers to challenge the theory as well as to extend the model such as tax preference theory, bird-in-the-hand theory, clientele hypothesis, and many more. However, for this paper, the theoretical review comprises of two most important fundamental principles for the dividend policy developed by different scholars and they are information asymmetries and behavioral factors.